2022
DOI: 10.1515/jisys-2022-0039
|View full text |Cite
|
Sign up to set email alerts
|

Short-term prediction of parking availability in an open parking lot

Abstract: The parking of cars is a globally recognized problem, especially at locations where there is a high demand for empty parking spaces. Drivers tend to cruise additional distances while searching for empty parking spaces during peak hours leading to problems, such as pollution, congestion, and driver frustration. Providing short-term predictions of parking availability would facilitate the driver in making informed decisions and planning their arrival to be able to choose parking locations with higher availabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…The installation of sensors and other infrastructure for data collection may be costly, as well as the development and maintenance of predictive models. When considering the cost of constructing parking occupancy forecasting models at the city level, one must take into account not only the creation and maintenance of individual models for single parking sites but also the time and resources necessary for implementing city-wide solutions [31].…”
Section: Spatiotemporal Correlations Between Parking Lotsmentioning
confidence: 99%
“…The installation of sensors and other infrastructure for data collection may be costly, as well as the development and maintenance of predictive models. When considering the cost of constructing parking occupancy forecasting models at the city level, one must take into account not only the creation and maintenance of individual models for single parking sites but also the time and resources necessary for implementing city-wide solutions [31].…”
Section: Spatiotemporal Correlations Between Parking Lotsmentioning
confidence: 99%
“…Moreover, finding parking spaces for an ever-growing number of vehicles exacerbates this issue. Drivers seek to find available spots close to their destinations to minimize walking distances, but this search for parking can cause traffic congestion and decrease vehicle speed; some studies have shown that almost 30% of urban traffic is due to drivers searching for parking spots [3]. The issue of traffic congestion and limited parking spaces is becoming a worldwide problem.…”
Section: Introductionmentioning
confidence: 99%
“…The research by ref. [3] involves a comparison of various prediction methods for parking spaces, including deep learning, standard machine learning, and classical methods. The methods they examined include long short-term memory from deep learning, seasonal autoregressive integrated moving average as a classical method, and the ensemble-based decision trees as a general method of deep learning.…”
Section: Introductionmentioning
confidence: 99%
“…In the recent years, various deep learning algorithms are used to forecast parking space availability. For example, Fan et al (2022) and Paidi (2022) use the long short-term memory (LSTM)…”
Section: Introductionmentioning
confidence: 99%